Effects of Thickness and Curvature on Impact Behaviour of Composite Panels - Usta, Fatih; Mullaoglu, Fehmi; Turkmen, Halit S.; Balkan, Demet; Mecitoglu, Zahit; Kurtaran, Hasan; Akay, Erdem (Elsevier Science Bv, 2016)
In this study, thickness and curvature effects on high velocity impact behavior of flat and cylindrical panels are investigated numerically. Four different samples are analyzed by using LS-DYNA software and the results are compared with regard to the absorbed energy, contact force, reaction force on the boundaries, displacement at the center of the backplane surface and residual velocity of the impacting object. Penetration values of projectile and contact forces of the cylindrical panels are higher than those for flat panels. Ply vibration leads to high contact force, especially for the 8-ply cylindrical panel. (C) 2016 The Authors. Published by Elsevier Ltd.
2nd International Symposium on Dynamic Response and Failure of Composite Materials, (Draf) -- SEP 06-09, 2016 -- Naples, ITALY
Keywords: Composite panel; Projectile impact; Absorbed energy; Cylindrical panel